Analisis Hukum Kausalitas Menggunakan Metode Social Explanation: Studi Kasus Kasus Kopi Sianida Mirna Salihin - E.P. Sembiring, Maekel; Hadi Purnomo (Pusat Penelitian dan Pengembangan Polri, 2024)
The concept of causality in criminal law is a fundamental element that determines the relationship between actions and consequences, which is essential in upholding criminal responsibility. The cyanide coffee poisoning case involving Jessica Wongso and Mirna Salihin highlights the complexity of applying the theory of causality, where the interaction between personal motives and actions leads to fatal consequences. This research aims to delve into the application of causality theory in criminal law in the case of cyanide-laced coffee poisoning involving Jessica Wongso and Mirna Salihin. The research method used is content analysis by referring to relevant literature sources related to causality theory in criminal law. The results of the study indicate that the concept of causality law becomes the main focus in determining criminal responsibility, where the importance of an action as a cause of a consequence that violates legal norms is the main concern in the analysis and assessment of the relevant actions. In the context of the cyanide-laced coffee poisoning case, the analysis of causality law using the Social Explanation method provides a deep understanding of the application of causality theory in criminal law. Thus, this research provides in-depth insights into the concept of causality in the realm of criminal law, especially in cases involving the infamous poisoning incident and cyanide elements.